Perilaku Konsumen Produk Lipcream Wardah (Studi Pada Mahasiswi Fakultas Ekonomi dan Bisnis Universitas Jember Kampus Bondowoso) - Zainuri Zainuri; Septarina Prita Dania S; Isrofiatullaily Putri Giani (Universitas Islam Lamongan, 2022)
Women and cosmetics are inseparable, nowadays. This condition is also responded positively by cosmetic companies ranging from new product innovations to price promotions. The number of new products certainly has its assessment for regular customers. This research focuses on the Faculty of Economics and Business students at the University of Jember in Jember and Bondowoso. This study examines the effect of halal certificate, prices, and brand image on consumer loyalty to Wardah’s lip cream products which have won top brand awards for the last three years. The study uses linear regression analysis and SPSS 25 software. The research findings reveal that the halal label variable does not affect consumer’s loyalty. Price and brand image variables has significant positive effects on consumer’s loyalty.